The Ecosystem of Learning: Admission and Diversity in Christian Higher Education. Issue 5 (20th October 2021) - Collins, Christopher S.; Mathew, Allan; Paredes-Collins, Kristin
Abstract: The policies, priorities, and productivity of postsecondary admission offices are under a great deal of scrutiny. The current realities range from the pressures of tuition-driven institutions to deliver the majority of the university budget each fall, to more selective institutions wrestling with standards of which applicants to accept amid national scandals such as the well-publicized "varsity blues" (a conspiracy to influence admission decisions at several top U.S. universities that was uncovered in 2019). Historically, institutional guidelines related to the admission and rejection of applicants have maintained a tense relationship with issues related to homogeneity and diversity. Postsecondary institutions in the U.S. were originally developed for the purpose of educating wealthy White men and slowly expanded to include more groups, in principle, even if not manifested in actual enrollment composition. Notably, efforts to diversify have repeatedly put admissions issues back in the spotlight of the U.S. Supreme Court. This article identifies and describes the process of admission to institutions of Christian higher education as one of the earliest points of contact for creating a learning environment. By taking an ecosystem approach akin to the metaphor of the body in I Corinthians 12, we examine the benefits of diversity in a manner that recognizes the ways in which all parts of the body can benefit, when all parts of the system are considered and included. Conversely, monocultures can miss the benefits of diversity, a reality that should be considered given that the process of shaping a class is often under the purview of admission and recruitment personnel. Beyond the more typical concerns related to the budget or prestige of an institution, shaping the class is critical to the process of creating a diverse learning environment that also provides multifaceted opportunities for cultivating spiritual growth.